Rhodium(III)-Catalyzed C–C Bond Formation by Direct C–H Activation - Li, Xiaolan; Luo, Haiqing (Synlett, 2025)
Transition-metal-catalyzed functionalizations of C–H bonds to construct C–C bonds represent an ideal route in the synthesis of valuable organic molecules. In particular, rhodium(III)-catalyzed C–H bond activation offers an attractive strategy due to its efficiency and step economy for direct functionalization in organic synthesis. Consequently, recent developments in this area have assured a high level of regioselectivity in C–H functionalization reactions. In this Account, we have summarized our recent achievements in the functionalizations of sp2- and sp3-C–H bonds using rhodium catalyst. The scope, limitation, and mechanism of these reactions have been described briefly.1 Introduction2 C–H Arylation2.1 Aromatic C(sp2)–H Arylation2.2 Benzylic C(sp3)–H Arylation2.3 Olefinic C(sp2)–H Arylation3 Olefinic C(sp2)–H Alkenylation and Alkylation4 Olefinic C(sp2)–H Heteroarylation5 Conclusion
Keywords: rhodium(III)-catalyzed; C–H activation; arylation; alkenylation; alkylation; heteroarylation